Management Stategik Badan Usaha Milik Daerah (BUMD) - Rayanto, Tavip Agus (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 1998)
As one of the potential source of local government revenue, it seems that the Local Government Owned Enterprise (Badan Usaha Milik Daerah BUMD) have contributed very little to the whole Local Government Revenue (Pendapatan Asli Daerah). It is also ironic that insofar the existence of BUMD has been much rely on the government regulation and given monopoly in its business. The ambiguous mission of BUMD Ã¢â¬â between an agent of development and a profit center Ã¢â¬â proved to be the main obstacle for its management system. From the strategic management perspective and SWOT analysis, it is found out that BUMD should adopt a turn-around approach, to minimize its weaknesses and try to get maximum benefit of the wide-opened opportunities. The strategic issues to be tackled by the BUMD management are quite complex. But among the most important issues are: the lack of professional human resources, the inflexible organisational structure and the low product or service quality. To address these issues, it is recommended that BUMD would come up with strategic human resource development programs, to apply more adaptive and flat organisational structure, and to adopt Total Quality Management (TQM) system in order to be more responsive to its customers.